Assessment of Complex Flow Patterns in Patients With Carotid Webs, Patients With Carotid Atherosclerosis, and Healthy Subjects Using 4D Flow MRI - El Sayed, Retta; Park, Charlie C.; Shah, Zahraw; Nahab, Fadi B.; Haussen, Diogo C.; Allen, Jason W.; Oshinski, John N. (Journal of magnetic resonance imaging, 2024)
Background Carotid webs (CaWs) are fibromuscular projections in the internal carotid artery (ICA) that cause mild luminal narrowing (<50%), but may be causative in up to one‐third of seemingly cryptogenic strokes. Understanding hemodynamic alterations caused by CaWs is imperative to assessing stroke risk. Time‐Average Wall Shear Stress (TAWSS) and Oscillatory Shear Index (OSI) are hemodynamic parameters linked to vascular dysfunction and thrombosis. Purpose To test the hypothesis: “CaWs are associated with lower TAWSS and higher OSI than mild atherosclerosis or healthy carotid bifurcation.” Study Type Prospective study. Population A total of 35 subjects (N = 14 bifurcations with CaW, 11F, age: 49 ± 10, 10 mild atherosclerosis 6F, age: 72 ± 9, 11 healthy 9F, age: 42 ± 13). Field Strength/Sequence 4D flow/STAR‐MATCH/3D TOF/3T MRI, CTA. Assessment 4D Flow velocity data were analyzed in two ways: 1) 3D ROI in the ICA bulbar segment (complex flow patterns are expected) was used to quantify the regions with low TAWSS and high OSI. 2) 2D planes were placed perpendicular to the centerline of the carotid bifurcation for detailed analysis of TAWSS and OSI. Statistical Tests Independent‐samples Kruskal–Wallis‐H test with 0.05 used for statistical significance. Results The percent surface area where low TAWSS was present in the ICA bulb was 12.3 ± 8.0% (95% CI: 7.6–16.9) in CaW subjects, 1.6 ± 1.9% (95% CI: 0.2–2.9) in atherosclerosis, and 8.5 ± 7.7% (95% CI: 3.6–13.4) in healthy subjects, all differences were statistically significant (ƞ2 = 0.3 [95% CI: 0.05–0.5], P‐value CaW vs. healthy = 0.2). OSI had similar values in the CCA between groups (ƞ2 = 0.07 [95% CI: 0.0–0.2], P‐value = 0.5), but OSI was significantly higher downstream of the bifurcation in CaW subjects compared to atherosclerosis and normal subjects. OSI returned to similar values between groups 1.5 diameters distal to the bifurcation (ƞ2 = 0.03 [95% CI: 0.0–0.2], P‐value = 0.7). Conclusion Lower TAWSS and higher OSI are present in the ICA bulb in patients with CaW when compared to patients with atherosclerotic or healthy subjects. Evidence Level 2 Technical Efficacy Stage 2